2000
DOI: 10.1016/s0042-6989(99)00185-6
|View full text |Cite
|
Sign up to set email alerts
|

The discrimination of abrupt changes in speed and direction of visual motion

Abstract: A random dot pattern that moved within an invisible aperture was used to present two motions contiguously in time. The motions differed slightly either in speed (Experiments 1 and 3) or in direction (Experiments 2 and 4) and the subject had to discriminate the sign of the change (e.g. increment or decrement). The same discrimination task was performed when the two motions were temporally separated by 1 s. In Experiments 1 and 2 discrimination thresholds were measured with motion durations of 0.125, 0.25, 0.5 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 20 publications
2
16
0
Order By: Relevance
“…Results from speed and direction discrimination studies show a somewhat more complicated behavior than position perception. Up to speeds of 64°/sec (close to the peak velocity measured in our experiments), Weber fractions for speed decrease to a minimum of 0.08 for viewing durations of 500 msec (Mateef et al, 2000). These results are consistent across a number of studies and types of stimuli (Orban et al, 1985;De Bruyn and Orban, 1988).…”
Section: Methodssupporting
confidence: 89%
“…Results from speed and direction discrimination studies show a somewhat more complicated behavior than position perception. Up to speeds of 64°/sec (close to the peak velocity measured in our experiments), Weber fractions for speed decrease to a minimum of 0.08 for viewing durations of 500 msec (Mateef et al, 2000). These results are consistent across a number of studies and types of stimuli (Orban et al, 1985;De Bruyn and Orban, 1988).…”
Section: Methodssupporting
confidence: 89%
“…Up to speeds of 64°/s (close to the peak velocity measured in our experiments), Weber fractions for speed decrease to a minimum of .08 for viewing durations of 500 ms (Mateeff, Dimitrov et al 2000). These results are consistent across a number of studies and types of stimuli (Orban, Van Calenbergh et al 1985; De Bruyn and Orban 1988).…”
Section: Methodssupporting
confidence: 76%
“…Psychophysical studies have shown that humans have a Weber fraction for motion discrimination of 0.08 (Mateef et al, 2000). Further, this value is largely invariant to the retinal eccentricity of the motion.…”
Section: Modeling the Motor Systemmentioning
confidence: 99%